Aplicación de las capacidades coordinativas para el desarrollo psicomotriz y su incidencia en los alumnos de primero a septimo año de educación básica de la escuela “Adolfo Jurado Gonzalez” de la cuidad de Loja - Pardo Vera, Byron Rodrigo (2014)
This research titled "APPLICATION OF coordinative capacities psychomotor DEVELOPMENT AND ITS IMPACT ON STUDENTS from FIRST grade TO SEVEN grade in " ADOLFO JURADO GONZALEZ SCHOOL " of Loja" explains and analyze the state of the educational approach in the school context within the field of physical education in their teaching practice-applicative nature socio-conceptual and theoretical dimensions; also determines the operation that gives the teacher the Planning Curriculum performed by blocks according to the institutional reality in physical education classes; and sequencing of planning the PE teacher performed in different classes taught to students. This is a study of application, quantitative, descriptive and correlation, focused mainly on analyzing the basic motor skills, and the fulfillment of specific targeted objectives: keep track of their development process, know the method by which teacher imparted his teaching without forgetting the National Plan for Education, and identify which activities implemented in teaching were not of interest in school. To do the research population corresponded to one teacher and 60 students “ADOLFO JURADO GONZALEZ SCHOOL" of Loja. Time, motivation, environment, resources, materials and teaching methods that students use and receive for the implementation of the development of psychomotor skills and coordinative skills. This information was revealed in previously prepared survey. The results show the existence of an inappropriate operation of the Curriculum blocks according the planning of the institutional reality in physical education classes and how this failure significantly affects the improvement of coordinative Physical Capabilities for psychomotor development of students.